Chapter 18: An accounting framework recognising the complexity of the nexus - Giampietro, Mario (Edward Elgar Publishing, 2022)
This chapter presents a structured approach to quantitative analysis of the water-energy-food resource nexus based on the multi-scale integrated analysis of societal and ecosystem metabolism (MuSIASEM) accounting framework. Concerning a social-ecological system of interest, the presented approach focuses on addressing: (i) system size and state; (ii) the environmental pressures associated with a particular size and state; (iii) the level of system openness, referring primarily to the role of externalization in the stabilization of both state and pressure; and (iv) the ecological impacts resulting from a localized contextualization of environmental pressures. An integrated toolkit consisting of four criteria of performance, four data matrices and four scopes/lenses is presented. The presented toolkit is proposed to be used by sustainability analysts. In illustrating the value-added of the toolkit, practical considerations and empirical results concerning agriculture in Europe are presented.